Rare and Fatal Gastrointestinal Mucormycosis (Zygomycosis) in a COVID-19 Patient: A Case Report - Epifanio Silvino do Monte Junior; Marcos Eduardo Lera dos Santos; Igor Braga Ribeiro; Gustavo de Oliveira Luz; Elisa Ryoka Baba; Bruno Salomão Hirsch; Mateus Pereira Funari; Eduardo Guimarães Hourneaux de Moura (Korean Society of Gastrointestinal Endoscopy, 2020)
The novel coronavirus disease (COVID-19) quickly spread to all continents. However, data regarding all the signs and symptoms of COVID-19 are insufficient. Patients with COVID-19 might present higher susceptibility to fungal coinfections. Mucormycosis is a rare and often life-threatening fungal disease characterized by vascular invasion by hyphae, resulting in thrombosis and necrosis. This is the first case report of mucormycosis in a COVID-19 patient. An 86-year-old male patient was admitted to the emergency room with acute diarrhea, cough, dyspnea, and fever from 5 days prior. Blood tests revealed a hemoglobin level of 14.3 mg/dL. Five days following the admission, the patient presented with melena and a hemoglobin level of 5.6 mg/dL. A transfusion of three units of red blood cells was required. Esophagogastroduodenoscopy revealed two giant gastric ulcers with necrotic debris and a deep hemorrhagic base without active bleeding. Furthermore, biopsies confirmed mucormycosis. Despite intensive care, the patient died 36 hours after the esophagogastroduodenoscopy.